Palliative care for children and adults with inherited metabolic disease in Europe: an underutilised service for supportive treatment and care - Lee, Anja; Bliksrud, Yngve Thomas; Onali, Michela; Neugebauer, Julia; Eyskens, Francois; Haas, Dorothea; Mossler, Karin; Enekwe, Antije; Kiec-Wilk, Beata; Diep, Lien My; Bellettato, Cinzia Maria; Zernikow, Boris; et al. (Journal of inherited metabolic disease, 2025)
Palliative care should be an integral part of follow-up for patients with life-limiting/life-threatening conditions, irrespective of age and diagnosis. Many patients with inherited metabolic disorders (IMD) have palliative care needs due to multi-systemic conditions without curative treatment options. To map the organisation and accessibility of palliative care across European IMD expert centres, and to explore the experiences of IMD physicians with palliative care, the European Reference Network for Hereditary Metabolic Disorders (MetabERN) invited physicians from all 103 member institutions to participate in a survey covering various aspects of palliative care. Ninety-two physicians from 63 institutions in 23 countries participated. A national plan or strategy for palliative care had been established in most countries (87%). Both children (91%) and adults (89%) had access to palliative care services. Most paediatric (86%) and many adult IMD physicians (67%) used advance care planning. A total of 284 referrals to palliative care were reported, mostly IMD patients with lysosomal and mitochondrial disorders, and neurological, respiratory, cognitive and gastrointestinal comorbidities. However, during the past 5 years, the majority of physicians (60%) had referred 20% or fewer of their deceased patients to palliative care. Although palliative care is available in most European IMD expert centres, only a small proportion of deceased IMD patients has been referred. The findings of this study indicate both a misconception and underutilisation of modern palliative care services. Addressing existing barriers is essential, and both IMD physicians and patients may need more information about available palliative care services and up-to-date indications for referral.
Zuerst veröffentlicht: 25. Oktober 2025
Gesehen am 17.12.2025